2021
DOI: 10.1108/ajim-04-2021-0118
|View full text |Cite
|
Sign up to set email alerts
|

Exploring information seeking of rural older adults during the COVID-19 pandemic

Abstract: PurposeThis study investigates the impact of the COVID-19 pandemic on the types and sources of information sought by older adults along with their motivations in the Midwestern United States.Design/methodology/approachInterviews were conducted with 30 older adults residing in rural communities around the Midwestern United States during late-summer (July/August) 2020, using a protocol based on Dervin's Sense-Making Methodology. The resulting data was analyzed using standard content analysis procedures, guided b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…However, older people got less information about COVID-19 from the special patient’s association, the Ministry of Health telephone system, and newspapers/magazines. Consistent with these findings, a study in the USA ( Lund & Ma, 2022 ) found that older adults are more likely to receive health information about COVID-19 through friends and acquaintances and the television. Another study in China ( Chen, Gao, et al, 2020 ) found that people prefer to use traditional sources such as radio, television, newspapers, and friends and acquaintances to obtain health information about COVID-19 compared to modern sources.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, older people got less information about COVID-19 from the special patient’s association, the Ministry of Health telephone system, and newspapers/magazines. Consistent with these findings, a study in the USA ( Lund & Ma, 2022 ) found that older adults are more likely to receive health information about COVID-19 through friends and acquaintances and the television. Another study in China ( Chen, Gao, et al, 2020 ) found that people prefer to use traditional sources such as radio, television, newspapers, and friends and acquaintances to obtain health information about COVID-19 compared to modern sources.…”
Section: Discussionmentioning
confidence: 67%
“…Inconsistent with the present study’s findings, a study in China ( Zhao et al, 2020 ) found that websites are an important source of health information about COVID-19 in older adults. These discrepancies may be due to differences in information sources, facilities, and personal preferences of older adults based on cultural, economic, and social assumptions in different countries ( Chen, Gao, et al, 2020 ; Lund & Ma, 2022 ; Zhao et al, 2020 ). Therefore, it is very important to provide health information about COVID-19 in the elderly based on accessibility, resources, and facilities available ( Liu, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In January 2020, the World Health Organization (WHO) declared the COVID-19 outbreak a public health emergency of international concern, and on 11 March 2020, it declared it a global pandemic. The world was informed of its high potential for international spread, and warnings were issued about the consequences and impacts on the public health, social, and economic sectors of nations [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to [ 17 , 18 ], this situation generated an interest among the population in obtaining information about the pandemic, with people constantly exposed to news about risks that deepened feelings of concern and personal vulnerability. According to [ 19 , 20 ], part of the information disseminated by the media was that the highest mortality from COVID-19 occurred in people over 60 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…The elderly are particularly vulnerable to becoming severely ill from COVID-19, increasing the urgency for tailored communication strategies [50]. This preference for mass media as initial sources of information conflicts with previous findings suggesting that older adults rely on interpersonal sources such as health care providers and family members, not only for information but also to satisfy emotional needs stemming from social isolation during the pandemic [51,52]. One rationale for this inconsistency might be that the COVID-19 pandemic morphed into a political wedge issue in which risk perceptions, conspiracy beliefs, and responses to government recommendations were demarcated along partisan lines [6,53,54].…”
Section: Sociodemographics Driving Covid-19 Information-seeking Agementioning
confidence: 97%